The Effect of Economic Growth, Inflation and VAT (Value Added Tax) on the profitability of Automotive Sector companies listed on the IDX - Nasrudin, Moch. Andik; Puspasari, Ismayantika Dyah (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: This study aims to analyse the effect of macroeconomic factors, specifically economic growth, inflation, and VAT, on the profitability of companies in the automotive sector in Indonesia. Design/Method/Approach: This research uses a quantitative causality approach. The data used is secondary data obtained from the company's financial statements and macroeconomic indicators obtained from the Central Bureau of Statistics and the Ministry of Finance Website. Research Finding: The results showed that economic growth has a positive and significant effect on corporate profitability, while inflation and VAT have no significant effect. This finding indicates that the increasing purchasing power of the community along with economic growth contributes to the increase in corporate profits. Theoretical contribution/Originality: This study contributes to enriching the literature on the relationship between macroeconomic factors and firm profitability, particularly in the automotive sector. This study also adds a new perspective on the influence of macroeconomic conditions on corporate financial performance. Practitionel/Policy implication: The results of this study can be used by business people and policy makers to design more adaptive business strategies in the face of changing macroeconomic conditions. Companies can focus more on operational efficiency and price adjustment strategies to reduce the impact of inflation and taxation policies on profitability. Research limitation: This study has some limitations, such as the scope of the study being limited to the automotive sector in Indonesia, so the results may not be generalisable to other sectors. In addition, other external factors, such as interest rates and currency exchange rates, were not analysed in depth. Therefore, future research is recommended to expand the scope of the industry sectors studied and consider more macroeconomic variables in order to obtain a more comprehensive understanding of the factors that affect company profitability.